An Overview of the Palm Oil Plantation Industry and its Social Impact on Local Communities in Jambi Province, Sumatra, Indonesia - Aziz, Arfan; Armaz, Eja; Rafidah, Rafidah; M. Nazori; Rosmanidar, Elyanti; Mutia, Agustina; Usdeldi, Usdeldi; Anita, Efni; Fusfita, Nurlia; Rahma, Sri; M. Subhan; Nofriza, Eri; Alawiyah, Rabiyatul (International Journal of Economics (IJEC), 2024)
This study aims to provide a comprehensive overview of the palm oil plantation industry and its social impacts on local communities in Jambi Province, Sumatra, Indonesia. Palm oil plantations have become an important economic sector in the region, contributing significantly to the local and national economy. However, on the other hand, the expansion of this industry has also given rise to a variety of complex social and environmental problems. This study uses a qualitative approach with in-depth interviews, field observations, and document analysis to examine the socio-economic impacts on local communities. The results show an increase in the economic welfare of local communities through job creation and infrastructure improvements. However, negative impacts such as land conflicts, environmental degradation, and changes in culture and traditional livelihoods were also found. This study underlines the need for more sustainable and equitable policies in the management of palm oil plantations to minimize negative impacts on local communities and the environment in Jambi Province.